Reasons for not working from home in an ideal worker culture: Why women perceive more cultural barriers - Yvonne Lott; Anja Abendroth (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2019)
The present study analyzes workers' reasons for not working from home in German workplaces. We ask to what degree cultural barriers, besides technical barriers, are reasons for not working from home. The analyses are based on the second wave (2014-15) of the German Linked Personnel Panel (LPP). Factor analyses confirm the importance of technical and cultural barriers to working from home. Linear regression analyses show that because men work more often than women in areas where working from home is technically unfeasible, they are more likely to perceive job unsuitability of working from home. Women - independent of their status positions - are more likely not to work from home due to perceived cultural barriers. In workplaces with a pronounced ideal worker culture, employees are more likely to perceive cultural barriers to working from home. Finally, company-level work-life balance support diminishes perceived cultural barriers.
Keywords: 330